Enunciação e regularidades gramaticais: apontamentos para o ensino de língua portuguesa para o ensino médio - Elke Beatriz Felix Pena (2015)
In this work, we developed a study based on Semantics of Enunciation, in order to proposea kind of grammar teaching for high school that takes into account both the organic andenunciative dimensions of language. In order to do so, we Analyzed chapters dedicated tothe syntax in three collections of Portuguese language textbooks for high school. From thisanalysis, we discuss both the concepts of context and completeness of meaning, BYpresenting both the concepts of intertext and saturation in the enunciative event. Throughthis, we propose a teaching approach that considers both the notions of syntactic places andexamples-hive. Thus, we undertook a job with sentences in the classroom that addresses aset of examples related to each other in order to make students notice, through differentutterances of linguistic forms, the relationship between language and its externality. Forthis, we rely on the studies of Benveniste, Guimarães, Dias, Milner, Pecheux, Adam,Rastier, among other theorists. From the perspective we adopted during the event, definedby a certain enunciative scene, the subject mobilizes and updates his/her knowledges of thememory of sayings. When updating that memory is that, in parallel, both the effects ofmeaning and subject position are produced.